Australian health care providers' views on opt-out HIV testing - Leidel, S.; McConigley, Ruth; Boldy, Duncan; Wilson, Sally; Girdler, Sonya (BioMed Central Ltd., 2015)
Background: Opt-out HIV testing is a novel concept in Australia. In the opt-out approach, health care providers (HCPs) routinely test patients for HIV unless they explicitly decline or defer. Opt-out HIV testing is only performed with the patients' consent, but pre-test counselling is abbreviated. Australian national testing guidelines do not currently recommend opt-out HIV testing for the general population. Non-traditional approaches to HIV testing (such as opt-out) could identify HIV infections and facilitate earlier treatment, which is particularly important now that HIV is a chronic, manageable disease. Our aim was to explore HCPs' attitudes toward opt-out HIV testing in an Australian context, to further understanding of its acceptability and feasibility. Methods: In this qualitative study, we used purposeful sampling to recruit HCPs who were likely to have experience with HIV testing in Western Australia. We interviewed them using a semi-structured guide and used content analysis as per Graneheim to code the data. Codes were then merged into subcategories and finally themes that unified the underlying concepts. We refined these themes through discussion among the research team. Results: Twenty four HCPs participated. Eleven participants had a questioning attitude toward opt-out HIV testing, while eleven favoured the approach. The remaining two participants had more nuanced perspectives that incorporated some characteristics of the questioning and favouring attitudes. Participants' views about opt-out HIV testing largely fell into two contrasting themes: normalisation and routinisation versus exceptionalism; and a need for proof versus openness to new approaches. Conclusion: Most HCPs in this study had dichotomous attitudes toward opt-out HIV testing, reflecting contrasting analytical styles. While some HCPs viewed it favourably, with the perceived benefits outweighing the perceived costs, others preferred to have evidence of efficacy and cost-effectiveness.